Wybrane karty z dziejów wolborza. Materiały z konferencji naukowej z okazji 950-lecia miasta (10.X.2015). Red. Maria Wichowa. Łódź 2016: - - Sulejewicz-Nowicka, Monika (Prace Polonistyczne, 2019)
The reviewed volume of post-conference materials is a collection of two types of texts: about the past history of Wolborz, and about of its contemporary history. All works are characterized a high level of scientific and logical and consistent argument. The authors have developed important issues regarding the social, economic and intellectual life of Wolborz in the Middle Ages and during the Renaissance. Also, the researchers reconstructed the biographies of outstanding citizens of Wolborz. They used source, archival, printed and manuscript materials, literary and para-literary texts and online tools.